2018
DOI: 10.1140/epjc/s10052-018-6109-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoacoustic and Alfvénic black holes

Abstract: We introduce analogue black holes (BHs) based on ideal magnetohydrodynamic equations. Similar to acoustic BHs, which trap phonons and emit Hawking radiation (HR) at the sonic horizon where the flow speed changes from super-to sub-sonic, in the horizon of magnetoacoustic and Alfvénic BHs, the magnetoacoustic and Alfvén waves will be trapped and emit HR made of quantized vibrations similar to phonons which we call magnephonons and Alphonons. We proposed that magnetoacoustic and Alfvénic BHs may be created in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An Alfvénic black hole may be created using a magnetic flux tube with a variable cross section and super-Alfvénic flow. Using the linearized MHD equations in the presence of super-Alfvénic plasma flow, a tensorial form of the Alfvén waves (with an accompanying metric) was obtained (Gheibi et al 2018). The resultant metric is singular at a point (horizon of black hole) where the local Alfvén speed is equal to flow speed.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…An Alfvénic black hole may be created using a magnetic flux tube with a variable cross section and super-Alfvénic flow. Using the linearized MHD equations in the presence of super-Alfvénic plasma flow, a tensorial form of the Alfvén waves (with an accompanying metric) was obtained (Gheibi et al 2018). The resultant metric is singular at a point (horizon of black hole) where the local Alfvén speed is equal to flow speed.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In particular, we introduce a pair of canonical variables that specify the phase space of the underlying classical system and use the Dirac's canonical quantization prescription to write down the Alfvén wave velocity filed (or the corresponding plasma displacement vector) in terms of the creation and annihilation operators. This defines the concept of "Alphonons", the elementary excitations of the Alfvén wave velocity in a magnetized plasma that was first introduced in Gheibi et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…An immediate application of the concept of Alphonon was made by Gheibi et al (2018), who showed that in the horizon of an Alfvénic black hole, Alfvén waves will be trapped and emit Hawking radiation that comprises the Alphonons. Detecting the Hawking radiation from the gravitational black holes is an important task for scientists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation